Hydraulic and Thermal Performance of Microchannel Heat Sink Inserted with Pin Fins - Guo-Fu Xie; Lei Zhao; Yuan-Yuan Dong; Yu-Guang Li; Shang-Lin Zhang; Chen Yang (Micromachines, 2021)
With the development of micromachining technologies, a wider use of microchannel heat sink (MCHS) is achieved in many fields, especially for cooling electronic chips. A microchannel with a width of 500 μm and a height of 500 μm is investigated through the numerical simulation method. Pin fins are arranged at an inclined angle of 0°, 30°, 45°, and 60°, when arrangement method includes in-lined pattern and staggered pattern. The effects of inclined angle and arrangement method on flow field and temperature field of MCHSs are studied when Reynolds number ranges from 10 to 300. In addition to this, quantitative analyses of hydraulic and thermal performance are also discussed in this work. With the increase of inclined angle, the variation of friction factor and Nusselt number do not follow certain rules. The best thermal performance is achieved in MCHS with in-lined fines at an inclined angle of 30° accompanied with the largest friction factor. Arrangement method of pin fins plays a less significant role compared with inclined angle from a general view, particularly in the Reynolds number range of 100~300.